2018
DOI: 10.1002/ijgo.12575
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical associations of hypovitaminosis D in pregnant women from Brazil

Abstract: The rate of hypovitaminosis D in pregnant women from southern Brazil was high. Hypovitaminosis D was more common in winter and was associated with pre-eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Second, the DHBC is a prospective cohort with consecutive ongoing enrollment. Third, the size of the population is similar to -or larger thansimilar studies with a population of pregnant WLWH [29][30][31].…”
Section: Discussionmentioning
confidence: 90%
“…Second, the DHBC is a prospective cohort with consecutive ongoing enrollment. Third, the size of the population is similar to -or larger thansimilar studies with a population of pregnant WLWH [29][30][31].…”
Section: Discussionmentioning
confidence: 90%
“…The factors associated with the risk of vitamin D deficiency in pregnant women were being married, the use of vehicles as a means of transportation, blood collection in winter, only face and hands being exposed to the sun, preeclampsia, first pregnancy, adolescence, and low income [ 33 , 34 ]. However, a study with 226 women found no association between vitamin D deficiency and obstetric, biological, and socioeconomic variables [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D sufficiency (> 30 ng/mL) was found in 20.8% of mothers and 42.3% of newborns. Some studies in Brazil describe the 25(OH)D concentrations during pregnancy [ 10 , 11 , 14 ]. The prevalence of insufficiency/deficiency evidenced by them (range: 44.1% to 58.9%) was lower than this study, taking to account term birth (63.4%) and preterm birth (83.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies evaluated 25(OH)D concentrations in Brazilian pregnant women [ 10 , 11 , 14 ]. However, no studies have been published on women who have prematurely given birth with a gestational age of fewer than 32 weeks.…”
Section: Introductionmentioning
confidence: 99%